Empowerment Communication in Rural Community-Based Drug Abuse Rehabilitation Program in Banyumas - Gunawan, Yuni; Runtiko, Agus Ganjar; Prastyanti, Shinta (IKOMIK: Jurnal Ilmu Komunikasi dan Informasi, 2024)
This research investigates the role of empowerment communication in a community-based rehabilitation program for substance abuse in rural Banyumas, specifically focusing on Karangtengah Village. Adopting a focused ethnographic approach, the study aims to describe the local culture and wisdom, map the communication patterns among stakeholders involved in drug abuse prevention and rehabilitation, and analyze how empowerment communication is conducted within the village community.Karangtengah Village was selected by the Banyumas Regency National Narcotics Agency (BNNK) as a pilot project for the Community-Based Intervention (IBM) Program due to its status as a tourist buffer village, making it susceptible to drug abuse influences. The program utilizes Recovery Agents (AP), a team of five volunteers dedicated to assisting individuals experiencing mild drug abuse issues. The findings highlight that the village's communication dynamics are significantly shaped by social structures, livelihoods, and community institutions, all of which play crucial roles in daily interactions. The empowerment communication process is facilitated through various IBM services, including socialization, mapping, outreach, and mentoring. The study demonstrates that effective communication is pivotal in influencing actions within rural communities, with social capital and local wisdom serving as foundational elements. By enhancing social capital and promoting collective self-empowerment, effective communication fosters community involvement in their development and progress, particularly in community-based drug rehabilitation initiatives. This research contributes to communication science by showcasing the efficacy of empowerment communication rooted in local wisdom and social capital, thereby encouraging rural community engagement in drug rehabilitation efforts.